Interrelationship Between Orthodontics and Implantology in Anterior Aesthetic Rehabilitation: A Case Report - Cavalcante, Adailton de Morais; Medeiros, Renata Cordeiro Teixeira; Lima, Danilo Lopes Ferreira; Santos, Saulo Ellery (Journal of Dentistry Indonesia, 2021)
The rehabilitation of complex cases in the anterior region of the maxilla may require knowledge of several dental specialties. when dental involvement also causes bone and gingival involvement, management usually requires adjustment of gingival zenitis and bone graft to compensate for bone loss. Objective: to discuss a case of previous orthodontic treatment for implant-prosthetic rehabilitation in the anterior region. Case report: This case report describes a 40-year-old patient who came with the intention of extracting the tooth and installing a bridge. The implant-prosthetic treatment was performed after previous orthodontic treatment to adapt the gingiva and space. Conclusion: The interrelationship of specialists in oral rehabilitation improved the aesthetic and functional result of this complex case. Orthodontic mechanics and periodontics adapted the space and improved the periodontal condition before the implant was installed, resulting in a very satisfactory aesthetic, improving the patient’s self-esteem.